2009
DOI: 10.1258/acb.2009.009080
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoproteins in diabetes dyslipidaemia in South Asians with young adult-onset diabetes: distribution, associations and patterns

Abstract: A large proportion of young adult Sri Lankan patients with type 2 diabetes has a low LDLC:apoB and high apoB and/or TG, suggesting that these patients are at increased risk of CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…23 In this study, Apo B/Apo A-I ratio shown good association with cardiometabolic risk markers, the positive correlation with various variables of study was observed except for HDL-C and Apo A-I. This study showed that, LDL, TC and TG were positively correlated with Apo-B and Apo-B was negatively correlated with HDL-C are in keeping with Kumar S et al 24 , and Katulanda GW et al 25 The combined effect of Apo B and Apo A-I is realized in the Apo B/Apo A-I ratio which showed a highly signi cant correlation with cardiometabolic risk biomarkers. Recent studies have used the Apo B/Apo A-I ratio is associated with cardiometabolic risk biomerkers.…”
Section: Discussionsupporting
confidence: 86%
“…23 In this study, Apo B/Apo A-I ratio shown good association with cardiometabolic risk markers, the positive correlation with various variables of study was observed except for HDL-C and Apo A-I. This study showed that, LDL, TC and TG were positively correlated with Apo-B and Apo-B was negatively correlated with HDL-C are in keeping with Kumar S et al 24 , and Katulanda GW et al 25 The combined effect of Apo B and Apo A-I is realized in the Apo B/Apo A-I ratio which showed a highly signi cant correlation with cardiometabolic risk biomarkers. Recent studies have used the Apo B/Apo A-I ratio is associated with cardiometabolic risk biomerkers.…”
Section: Discussionsupporting
confidence: 86%
“…Since women with diabetes have a higher rate of mortality from cardiovascular disorders than men [7], it could be hypothesized that increased levels of serum Lp(a) in women with diabetes, may be one of the mechanisms for this observation. On the other hand, one could think that these results are affected by the gender effect on serum Lp(a) levels which is demonstrated by population based studies [40]. We showed that the odds ratio of having a serum Lp(a) level higher than 35 was 5.85 in premenopausal women with diabetes, 5.08 in postmenopausal women with diabetes, 2.41 in men with diabetes and 1.9 in women of the control group compared to men of the control group, when adjusting for age and BMI.…”
Section: Discussionmentioning
confidence: 98%
“…Katulanda G et al, found that patients with type 2 diabetes had atherogenic lipid profiles [32]: elevated ApoB often accompanied by elevated TG, high Apo B100/ Apo A1 ratio and low LDL: Apo B 100 ratio. Sniderman AD et al, found in 249 Canadian subjects that 23% had abnormal LDL [33], i.e., an elevated LDL cholesterol level; almost 40% has an elevated Apo B and therefore an elevated LDL particle number.…”
Section: Discussionmentioning
confidence: 99%